Using a flipped classroom teaching and learning approach to promote scientific literacy skill development and retention - Elaina B. K. Brendel; Ala Alzubi; Shrujan Rai; Christine Mariathasan; Laelie A. Snook; Jennifer M. Monk (FEBS Open Bio)
The development of scientific literacy (SL) skills is critical in the life sciences. A flipped classroom reverses traditional learning spaces such that foundational knowledge is acquired by students independently through recorded lectures and/or readings in advance of the lecture period and knowledge is consolidated through active learning activities in the classroom. A flipped classroom learning environment can promote critical skill development and knowledge application, and therefore, could enhance SL skill development. The objectives here were to (a) determine the effect of a flipped classroom learning environment on SL skill development in second‐year kinesiology students enrolled in a research methods course and (b) reassess SL skills 4 months later. SL skills were assessed using the validated test of scientific literacy skills (TOSLS) questionnaire at the start and end of the semester (n = 57) and reassessed 4 months later after the summer semester break (n = 46). During the flipped classroom semester, practical SL skills (TOSLS scores) were increased by 16.3% and TOSLS scores were positively correlated with the students' final grade (r = 0.526, P < 0.001). Four months later, average TOSLS scores significantly decreased compared to the levels at the end of the flipped classroom learning experience. Importantly, retention of SL skills (i.e., 4 months later TOSLS scores) were related to learning approach scores and were positively correlated with deep learning approach scores (r = 0.298, P = 0.044) and negatively correlated with surface learning approach scores (r = −0.314, P = 0.034). Therefore, SL skill retention was higher in students utilizing a deep learning approach (e.g., engaged, self‐regulation in learning, and seeking a deeper understanding of concepts) and lower in students utilizing a surface learning approach (e.g., limited engagement, rote memorization of concepts). Collectively, the results demonstrate the value of a flipped classroom in promoting SL skills while highlighting the role of students' learning approach in critical skill retention.